KETENTUAN HUKUM TERHADAP ANAK PELAKU PENYEBARAN HOAX MELALUI MEDIA SOSIAL MENURUT SISTEM PERADILAN PIDANA ANAK - Ellya Nur Fitriana (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
AbstractThe advancement of information and communication technology especially in social media applications such as Facebook, Intagram where most users are children, at least 30 million children as internet users as their main channel of communication. Illegal acts in cyberspace is a very worrying phenomenon, considering carding, hacking, fraud, terrorism and destructive information dissemination (hoaxes) have become part of the activities of perpetrators of cyber crime.The incomplete maturity of children's thinking to process information is vulnerable to being provoked and spreading hoax news on social media. Child delinquency is also referred to as Juvenille Deliquency or referred to as a disabled child. Examples of cases that are rampant occur the circulation of abduction issues spread by 16-year-olds by posting on their Facebook groups.Criminal Provisions in Law Number 11 Year 2008 concerning Information and Electronic Transactions Article 45 Paragraph (2) states that everyone who fulfills the elements referred to in Article 28 paragraph (1) and (2) is punished with imprisonment of a maximum of 6 years and / or a maximum fine of 1,000,000,000.00 (one billion rupiah).The results of the study and discussion are known that Based on the Child Criminal Justice System Act, a child who commits a crime spreads false news or hoaxes through an investigation and is seen from the criminal provisions offenses under 7 years will seek a diversion process, namely the transfer of settlement of child cases from criminal justice processes to processes outside of criminal justice.